2018
DOI: 10.1128/aem.02510-17
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Waterborne Pathogen Presence and Aiding Source Apportionment in an Impaired Stream

Abstract: Fecal indicator bacteria (FIB) are the basis for water quality regulations and are considered proxies for waterborne pathogens when conducting human health risk assessments. The direct detection of pathogens in water and simultaneous identification of the source of fecal contamination are possible with microarrays, circumventing the drawbacks to FIB approaches. A multigene target microarray was used to assess the prevalence of waterborne pathogens in a fecally impaired mixed-use watershed. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Filtration approaches that allow simultaneous concentration of a wide range of organisms are increasingly used to process samples, including as part of automated large-volume samplers, prior to culture or molecular detection [128,[154][155][156]. Ultrafiltration techniques in particular have demonstrated reasonably efficient and consistent recovery for a variety of organisms, water types, and sample volumes, providing a natural complement to multitarget arrays, and increasingly appear to be the default concentration approach for many applications [154,[157][158][159][160][161]. Co-concentration of qPCR inhibitors during ultrafiltration is a concern, but effective inhibition mitigation has been demonstrated by further processing of the concentrate prior to analysis [160,[162][163][164].…”
Section: Analytical Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Filtration approaches that allow simultaneous concentration of a wide range of organisms are increasingly used to process samples, including as part of automated large-volume samplers, prior to culture or molecular detection [128,[154][155][156]. Ultrafiltration techniques in particular have demonstrated reasonably efficient and consistent recovery for a variety of organisms, water types, and sample volumes, providing a natural complement to multitarget arrays, and increasingly appear to be the default concentration approach for many applications [154,[157][158][159][160][161]. Co-concentration of qPCR inhibitors during ultrafiltration is a concern, but effective inhibition mitigation has been demonstrated by further processing of the concentrate prior to analysis [160,[162][163][164].…”
Section: Analytical Sensitivitymentioning
confidence: 99%
“…The outsized influence of precipitation on microbial concentrations may obscure less dramatic dynamics in many systems [195]. Furthermore, clear long-term indicator trends do not necessarily represent concomitant changes in pathogen hazards [157].…”
Section: Applications and Recommendationsmentioning
confidence: 99%
“…The relationships between FIB and various pathogens in freshwater, and the individual studies from which they were derived, are summarized in Table 1. Of the 41 studies, approximately one third ( n = 18) [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52] did not report any relationship between indicators and pathogens measured. Of the remaining 23 studies, thirteen reported positive relationship between at least one indicator and one pathogen [53,54,55,56,57,58,59,60,61,62,63,64,65], while ten did not find significant relationships [66,67,68,69,70,71,72,73,74,75].…”
Section: Fib and Pathogens In Freshwatermentioning
confidence: 99%
“…with 22 measurements each, while Cryptosporidium and Giardia (oo)cysts were reported less frequently ( n = 6) (Table 4). Irrespective of the water type, nine of these studies did not report statistical analyses for relationships between MST marker(s) and pathogens [51,76,77,79,80,83,86,88,105], and another seven reported non-significant relationship [48,56,57,70,72,98,99]. The remaining two studies reported statistically significant relationship [93,106] (Table 4).…”
Section: Mst Markers and Pathogens In Marine Brackish And Freshwatermentioning
confidence: 99%
“…Waste byproducts from various forms of life within a watershed may be identified through microbial source tracking (Jiang et al, 2007;Ballesté et al, 2020), yielding insights into landscape ecology. Waste signals in stream waters may also be useful in understanding the fate and transport of certain waterborne pathogens (Weidhaas et al, 2018). Finally, but certainly not exhaustively, by literally shedding light on stream water samples, the resulting optical properties we observe may metaphorically shed light on the sources and processes operating on organic materials in watersheds (Fellman et al, 2010;Hosen et al, 2021).…”
Section: Introduction: Water Sends "Mixed Signals"mentioning
confidence: 90%